2005
DOI: 10.1093/molbev/msi164
|View full text |Cite
|
Sign up to set email alerts
|

Alu-SINE Exonization: En Route to Protein-Coding Function

Abstract: The majority of more than one million primate-specific Alu elements map to nonfunctional parts of introns or intergenic sequences. Once integrated, they have the potential to become exapted as functional modules, e.g., as protein-coding domains via alternative splicing. This particular process is also termed exonization and increases protein versatility. Here we investigate 153 human chromosomal loci where Alu elements were conceivably exonized. In four selected examples, we generated, with the aid of represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
112
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 27 publications
4
112
0
1
Order By: Relevance
“…The term 'exaptation' (or 'spandrels' [138]; §2.4.1) has been coined for such latent traits that arise by chance and may or may not evolve to have a new function [379]. Apart from point mutations, mobile genetic elements are likely to play a crucial role in providing exaptations [380][381][382]. Each genome appears to constantly produce transcribed and translated 'proto-genes' that arise by chance, some of which may be exapted by evolution for a certain function [383].…”
Section: Evolvability Hidden States and Promiscuous Functionsmentioning
confidence: 99%
“…The term 'exaptation' (or 'spandrels' [138]; §2.4.1) has been coined for such latent traits that arise by chance and may or may not evolve to have a new function [379]. Apart from point mutations, mobile genetic elements are likely to play a crucial role in providing exaptations [380][381][382]. Each genome appears to constantly produce transcribed and translated 'proto-genes' that arise by chance, some of which may be exapted by evolution for a certain function [383].…”
Section: Evolvability Hidden States and Promiscuous Functionsmentioning
confidence: 99%
“…Such co-opted or exapted modules can be derived from inter-or intragenic space and constitute novel protein-coding exons and regulatory regions such as promoters and enhancers (Brosius 2005b(Brosius , 2009Baertsch et al 2008;Rebollo et al 2012). 5 A prominent case is the exonization of parts of Alu elements, usually as alternatively spliced exons (Makalowski et al 1994;Nekrutenko and Li 2001;Sorek et al 2002;Lev-Maor et al 2003;Krull et al 2005;Shen et al 2011). Many such events are, over evolutionary time, not stable.…”
Section: Yesterday's Junk Could Become Tomorrow's Novel Gene Module mentioning
confidence: 99%
“…Should, over time, the novel splice variant happen to become beneficial, it will be under purifying selection and, by point mutations in and around splice signals, its ratio, in comparison to the canonical splice form, might change in its favor. In a phylogenetic study on primates, it has been shown that such exons derived from Alu elements are lost at a high rate in the trial and error mode, typical for the evolution of novelties (Krull et al 2005). A similar study involving all mammals and the older MIRs revealed that many of the events were already fixed and currently are under negative selection.…”
Section: Yesterday's Junk Could Become Tomorrow's Novel Gene Module mentioning
confidence: 99%
“…The tandem genomic duplication of a portion of coding sequences with an AGGT cryptic splice site was initially proposed by Rogers (11) as a mechanism to produce the boundaries of a new intron. Although this model was rejected almost immediately based on the lack of similarity at the boundaries of introns that were examined, this mechanism was revived 10 years later to explain the origin of introns in several fish genes (12).A new intron can also arise when a known boundary is spliced to a novel junction created by point mutations, as is the case with the exonization of Alu elements (13,14). Recently, an intron in the SETMAR gene was shown to originate from the exonization of a mariner-like Hsmar1 transposon (15).…”
mentioning
confidence: 99%
“…A new intron can also arise when a known boundary is spliced to a novel junction created by point mutations, as is the case with the exonization of Alu elements (13,14). Recently, an intron in the SETMAR gene was shown to originate from the exonization of a mariner-like Hsmar1 transposon (15).…”
mentioning
confidence: 99%